Valuing biodiversity of Dachigam National Park: a choice experiment application. Issue 6 (5th June 2020) - Bhat, Mohammad Younus; Bhatt, M.S.; Sofi, Arfat Ahmad
Abstract : Purpose: Biodiversity loss has become widespread since current rates are potentially catastrophic for species and habitat integrity, and the Dachigam National Park in Jammu and Kashmir (India) is not a distinctive case. Therefore, the main objective of this study is to elicit the willingness to pay (WTP) for biodiversity conservation of the Park. Design/methodology/approach: A survey-based choice experiment method was carried out at the Dachigam National Park, an area that is threatened by several anthropogenic pressures. Attributes selected for analysis through choice experiments were endangered species, national park area, research and education opportunities the park withholds. To estimate WTP, a monetary variable involving an increase in entry fee was also incorporated. To obtain the estimates, the authors use the augmented conditional logit model. Findings: WTP for the selected attributes per visitor turned out to be ₹302.07 for enhancing the population of endangered species, ₹121.91 for improvement in the park area and ₹171.64 for increasing research and education opportunities the park withholds. Research limitations/implications: Though the study uncovers very important aspects of evaluating the biological resources, albeit with some limitations. The study estimates WTP for biodiversity conservation using a conditional logit model, which is based on a specific area and population sample. It would be better if a broader sample is considered to trace out the findings for meaningful generalization. Besides, the results can be replicated for similar kinds of samples. Practical implications: With the use of benefits transfer method, this study aims to provide policymakers with useful information to manage biodiversity attributes across the Himalayan region. Originality/value: The main contribution of this study is to provide a critical understanding of the valuation to facilitate the concerned body for better planning and management of biological resources. The findings of the present study can be used as an indicator of the inherent economic importance of biological resources across the Himalayan range for their better management and conservation that can help in ensuring sustainable utilization of these resources.